Solve: 2 In 3 = In(x - 4)
Step-by-step explanation:
\(2 ln(3) = ln(x - 4) \)
For logarithms, this is a property
\( ln(x {}^{n} ) = n ln(x) \)
So we have
\( ln( {3}^{2} ) = ln(x - 4) \)
\( ln(9) = ln(x - 4) \)
If
\( ln(a) = ln(b) \)
a=b
So
\(9 = x - 4\)
\(13 = x\)
The basketball team will need 196 fluid ounces of Gatorade for their tournament. How many cups will this equal?
Answer:
24.5
Step-by-step explanation:
Helpppp mee yalll
Put the following equation of a line into slope-intercept form, simplifying all
fractions.
8x - 12y = -24
Answer:
y=2/3x+2
Step-by-step explanation:
8x-12y=-24
subtract 8x from both sides to come up with -12y=-8x-24
divide -12y by everything and get y=-8/-12x-24/-12
simplify and get y=2/3x+2
its all positive since a negative divided by another negative= a positive
can anyone help me with this? im confused
Answer:
1,2,3 and 6 are similar triangles by AA similarity
Step-by-step explanation:
1) ∠DEC ≅ ∠FEG {Vertically opposite angles}
DC // GF
∠ECD ≅ ∠EGF {Alternate interior angles}
∠EDC ≅ ∠EFG {Alternate interior angles}
ΔDEC & ΔFEG are similar triangles by AA similarity
2)MN // QP
∠LQP ≅ ∠QMN {Corresponding angles }
∠LPQ ≅ ∠PNM {Corresponding angles}
ΔLQP & ΔLMN are similar triangles by AA similarity
3) In ΔSYE ,
∠S = 180 - 90 - 39
∠S = 51°
In ΔCHW,
∠H = 180 - 51 - 90
∠H = 39
ΔSYE and ΔCHW
∠S ≅ ∠W = 51°
∠Y ≅ ∠C = 90°
∠E ≅∠H = 39°
ΔSYE & ΔWCH are similar triangles by AA similarity
6) ∠P ≅ ∠Z {Given}
∠PXQ ≅∠ZXY {Vertically opposite angles}
ΔPXQ & ΔZXY are similar triangles by AA similarity
Help me find this asap
Answer:
DQ = \(\frac{5}{(2-\sqrt{x})(2-\sqrt{x+h})(\sqrt{x}-\sqrt{x+h})}\)
Step-by-step explanation:
Given function is f(x) = \(\frac{5}{2-\sqrt{x}}\)
f(x + h) = \(\frac{5}{2-\sqrt{x+h} }\)
Therefore, indicated difference quotient will be,
DQ = \(\frac{f(x+h)-f(x)}{h}\)
Now we substitute the values in the difference quotient,
DQ = \(\frac{\frac{5}{2-\sqrt{x+h} }-\frac{5}{2-\sqrt{x}}}{h}\)
= \(\frac{5(2-\sqrt{x})-5(2-\sqrt{x+h})}{h(2-\sqrt{x})(2-\sqrt{x+h})}\)
= \(\frac{10-5\sqrt{x}-10+5\sqrt{x+h}}{h(2-\sqrt{x})(2-\sqrt{x+h})}\)
= \(\frac{-5\sqrt{x}+5\sqrt{x+h}}{h(2-\sqrt{x})(2-\sqrt{x+h})}\)
= \(\frac{5(-\sqrt{x}+\sqrt{x+h})}{h(2-\sqrt{x})(2-\sqrt{x+h})}\)
= \(\frac{5(-\sqrt{x}+\sqrt{x+h})(\sqrt{x}+\sqrt{x+h})}{h(2-\sqrt{x})(2-\sqrt{x+h})(\sqrt{x}+\sqrt{x+h})}\)
= \(\frac{5[(x+h)-x]}{h(2-\sqrt{x})(2-\sqrt{x+h})(\sqrt{x}+\sqrt{x+h})}\)
= \(\frac{5h}{h(2-\sqrt{x})(2-\sqrt{x+h})(\sqrt{x}+\sqrt{x+h})}\)
= \(\frac{5}{(2-\sqrt{x})(2-\sqrt{x+h})(\sqrt{x}+\sqrt{x+h})}\)
In a card game it is possible to have negative score. If Laura starts with a score is 10 what will be her new score if she loses 38 points ?
Answer:
28
Step-by-step explanation:
10-38=28
$&#:÷&#&;#&$;'ebsjdkeowkdbs;#&$;'fbxjrbxjr
Please help answer this
The specified scale factor of the dilation from S to M is 3/2 therefore, the scale factor of the dilation transformation from M to S is 2/3
What is a dilation transformation?A dilation is a transformation in which the lengths of the sides of the image are increased or decreased in the proportion, specified by a scale factor to the dimensions of the pre-image.
The specified scale factor from triangle S to triangle M = 3/2
3/2 = 1.5
Therefore, the length of the sides of triangle M are 1.5 times the lengths of the sides of triangle S
Let L represent the length of a side of triangle S, we get;
The length of the corresponding side on triangle M = 1.5 × L
The scale factor from triangle M to triangle S is found by taking the ratio of the corresponding sides of triangle S and M as follows;
Scale factor, SF, from M to S = Length of a side on triangle S ÷ Length of the corresponding side on triangle
Therefore;
\(SF = \dfrac{L}{1.5\cdot L} = \dfrac{1}{1.5}\)
1.5 = 3/2, therefore;
\(SF = \dfrac{1}{1.5} = \dfrac{1}{\frac{3}{2} } =\dfrac{2}{3}\)
Therefore, the scale factor from M to S is 2/3
Learn more about scale factor of a dilation here:
https://brainly.com/question/13005407
#SPJ1
If m∠A = m∠B and m∠A + m∠C = ∠D, then m∠B + m∠C = ∠D.
Which property is shown?
reflexive property
substitution property
symmetric property
transitive property
Answer:
substitution property
Step-by-step explanation:
When you replace m∠A in the second equation with its equal, as defined by the first equation, you are making use of the substitution property.
That property says you can replace anything by its equal.
Answer:
subsitution
Step-by-step explanation:
i jus took the quiz
The digits 0,1,2,3,4,5 and 6 are used to make 3 digit codes
In case where digits may be repeated, how many codes are numbers that are greater than 300 and exactly divisible by 5?
Answer:
345/5=69
Step-by-step explanation:
345/5=69
355/5=71
76th term of the arithmetic sequence 16, 14, 12, .
Answer:
-134
Step-by-step explanation:
to create an equation for this sequence we figure out so the equation can be 18-2n. n= the number of the term for the first term we put 1 in for n and we see 18-2(1)=16 which is the first term so its correct. now we put 76 in for n and here is the equation. 18-2(76)=-134
Please please help me I’ve tried soooo many times
value of u = 2
Hope it helps you...
Answer:
u = 2
Step-by-step explanation:
6u + 7 = 29 - 5u
6u + 5u + 7 = 29 - 5u + 5u
11u + 7 = 29
11u + 7 - 7 = 29 - 7
11u = 22
11u ÷ 11 = 22 ÷ 11
u = 2
Question 4 (1 point)
A diagonal is drawn across a rectangle with side lengths measuring 3 cm and 8 cm. Find the smaller of the
two angles formed between the diagonal and the sides.
a69.4°
b22°
c 70.1°
d 20.6°
please help me!! solve for
x.
Can anyone pls help I don't get this problem
The function operation (f.g)(x) is solved by finding the composite function of the functions.
The operation (f.g)(x)\((f.g)(x)= f(g(x))\\g(x) = \frac{1}{x} = f(\frac{1}{x})\\f(\frac{1}{x}): \frac{x}{2+x} \\(f.g)(x) = \frac{x}{2+x}\)
DomainThe domain of this function is given as
\(domain = x < -2 or x > -2\\Interval notation (- infinity , -2) U (-2, inifnity)\)
From the calculations above, the composite function is the ratio of x to x + 2, while the domain of this function moves from negative infinity to negative two and negative two to infinity.
Learn more on function domain here.
https://brainly.com/question/15532699
2(3x-6)-2x+1=25 solve for x
Answer:
Step-by-step explanation:
Step 1: Simplify both sides of the equation.
2(3x−6)−2x+1=25
(2)(3x)+(2)(−6)+−2x+1=25(Distribute)
6x+−12+−2x+1=25
(6x+−2x)+(−12+1)=25(Combine Like Terms)
4x+−11=25
4x−11=25
Step 2: Add 11 to both sides.
4x−11+11=25+11
4x=36
Step 3: Divide both sides by 4.
4x
4
=
36
4
x=9
Answer:
X = 6.5
Step-by-step explanation:
First we need to simplify and also remember the use of PEMDAS.
6x-12-2x+1=25
4x-11=25
Addition property of equality
4x=26
Division property of equality
x=6.5
Help with geometry homework
The lake frontage of lot B to the nearest tenth is; 70.5 yds
How to use similarity ratio?We know that;
Two figures are similar if their corresponding angles are congruent , and the ratios of the lengths of their corresponding sides are equal. This common ratio is called the scale factor .
Find the lake frontage (to the nearest tenth) of each lot shown;
184/(54 + 69 + 57) = A/54 = B/69 = C/57
Thus, the lake frontage of lot B to the nearest tenth is;
B/69 = 184/180
B = (184 * 69)/180
B = 70.5 yds
Read more about similarity ratio at; https://brainly.com/question/822659
#SPJ1
Please help me for 15 points
lol,j,bhkgkjhkhkhkhukgiuguk
Answer:
wioajfcskaljfcksjhnfkmdesdn,k obviously
Step-by-step explanation:
What is c0, c1 and ck?
By the ratio test, the first series converges if
\(\displaystyle \lim_{k\to\infty} \left|\frac{\frac{x^{k+1}}{k+10}}{\frac{x^k}{k+9}}\right| = |x| \lim_{k\to\infty} \frac{k+9}{k+10} = |x| < 1\)
while the second series converges if
\(\displaystyle \lim_{k\to\infty} \left|\frac{(k+1)(k+5)x^{k+1}}{k(k+4)x^k}\right| = |x| \lim_{k\to\infty} \frac{k^2+6k+5}{k^2+4k} = |x| < 1\)
So as long as |x| < 1, we have
\(\displaystyle h(x) = -(x+4) f(x) + 7x^2 g(x)\)
Distribute f(x) :
\(\displaystyle h(x) = -x f(x) - 4 f(x) + 7x^2 g(x)\)
Substitute f and g with their series representations:
\(\displaystyle h(x) = -x \sum_{k=0}^\infty \frac{x^k}{k+9} - 4 \sum_{k=0}^\infty \frac{x^k}{k+9} + 7x^2 \sum_{k=0}^\infty k(k+4)x^k\)
Simplify the powers of x :
\(\displaystyle h(x) = -\sum_{k=0}^\infty \frac{x^{k+1}}{k+9} - 4 \sum_{k=0}^\infty \frac{x^k}{k+9} + 7 \sum_{k=0}^\infty k(k+4)x^{k+2}\)
Shift the index in each sum as needed so that each one is written in terms of \(x^k\) :
\(\displaystyle h(x) = -\sum_{k=1}^\infty \frac{x^k}{k+8} - 4 \sum_{k=0}^\infty \frac{x^k}{k+9} + 7 \sum_{k=2}^\infty (k-2)(k+2)x^k\)
Pull out as many terms as needed from each sum so that they each start with the same index:
\(\displaystyle h(x) = -\left(\frac x9 + \sum_{k=2}^\infty \frac{x^k}{k+8}\right) - 4 \left(\frac19 + \frac x{10} + \sum_{k=2}^\infty \frac{x^k}{k+9}\right) + 7 \sum_{k=2}^\infty (k-2)(k+2)x^k\)
Condensing the series gives
\(\displaystyle h(x) = -\frac49 - \frac{23}{45}x + \sum_{k=2}^\infty \left(7(k-2)(k+2)-\frac1{k+8} - \frac4{k+9}\right)x^k\)
So, if
\(\displaystyle h(x) = \sum_{k=0}^\infty c_kx^k = c_0 + c_1x + c_2x^2 + \cdots\)
then it follows that
\(c_0 = -\dfrac49\)
\(c_1 = -\dfrac{23}{45}\)
and for k ≥ 2,
\(c_k = \displaystyle 7(k-2)(k+2)-\frac1{k+8} - \frac4{k+9}\)
k
9. The table shows the results from a study in which some patients were treated with a new
medical drug for sleeping disorders and others received a common sleeping pill. Use a 0.05
significance level to find the critical value needed to test for independence between the type of
sleeping pill and the presence of any adverse health condition.
Adverse health
condition reported
No adverse health
condition reported
00.004
03.841
00.751
0.100.
New Sleeping Pill Common Sleeping Pill
135
132
145
122
(1 point)
The critical value of the chi-squared statistic with a significance level of 0.05 is 3.84. Therefore, the correct answer is option B.
The null hypothesis in this case would be that there is independence between the type of sleeping pill and the presence of any adverse health condition.
The critical value needed to test for this is the chi-squared statistic with a significance level of 0.05.
To calculate the critical value, we first need to calculate the degrees of freedom, which is calculated by (rows-1) * (columns-1). In this case, the degrees of freedom is (2-1)*(2-1) = 1.
The critical value of the chi-squared statistic with a significance level of 0.05 is 3.84. This means that if the calculated chi-squared statistic is greater than 3.84, then we can reject the null hypothesis and claim that there is a significant relationship between the type of sleeping pill and the presence of any adverse health condition.
Therefore, the critical value of the chi-squared statistic with a significance level of 0.05 is 3.84. Therefore, the correct answer is option B.
Learn more about the critical value here:
https://brainly.com/question/14508634.
#SPJ1
Determine the value of y, if x is -1. y= | x |-4
what are the features of the function g if g(x)= f(x+4) +8
The domain, range, x-intercept, or y-intercept of g(x) = f(x + 4) + 8. The features of g depend on the corresponding features of f.
Given the function g(x) = f(x + 4) + 8, let's examine its features:
Domain:
The domain of the function g will be the same as the domain of the function f, which depends on the restrictions or constraints of f. However, it is important to note that shifting the input by 4 units (x + 4) does not inherently change the domain unless there are specific restrictions imposed by f.
Range:
Similar to the domain, the range of the function g will depend on the range of the function f.
x-intercept:
The x-intercept of a function is the point where the graph intersects the x-axis, meaning the y-coordinate is zero (y = 0). To find the x-intercept of g(x), we set g(x) = 0 and solve for x.
0 = f(x + 4) + 8
By subtracting 8 from both sides:
-8 = f(x + 4)
Since the exact value of x that makes f(x + 4) equal to -8. The x-intercept will depend on the behavior of f.
y-intercept:
The y-intercept of a function is the point where the graph intersects the y-axis, meaning the x-coordinate is zero (x = 0). To find the y-intercept of g(x), we substitute x = 0 into the function:
g(0) = f(0 + 4) + 8
g(0) = f(4) + 8
Again, the specific value of f(4) will depend on the behavior of the function f.
for such more question on function
https://brainly.com/question/14723549
#SPJ8
Question 3 Write a method that solves for x in the quadratic equation. The parameters are a, b, c, and boolean flag that indicates whether it will solve the equation with addition or subtraction in the numerator. 2-4ac ㄨㄧ- 2a Source: Wikipedia The method will return the value of x
On solving the providewd question we can say that, public static double solve(double a, double b, double c, boolean flag )
What is quadratic equation?A quadratic equation is a quadratic polynomial in one variable that looks like this: x = ax2 + bx + c. a 0. This polynomial has at least one solution since it is a second-order polynomial, according to the Fundamental Theorem of Algebra. The answer can actually work or be difficult.
public static double solve(double a, double b, double c, boolean flag)
{ double d = Math.sqrt(b*b - 4*a*c); if(flag)
{ return (-b + d) / (2*a); }
else { return (-b - d) / (2*a); } }
To know more about quadratic equation visit:
https://brainly.com/question/17177510
#SPJ4
A student solves the following problem:
Problem: 2(x−3)+3x=19
Step 1: 2x−6+3x=19
Step 2: 6x−6=19
Step 3: 6x−6 + 6=19 + 6
Step 4: 6x=25
Step 5: 6x6=256
Step 6: x≈4.17
Where is the mistake? What did the student do incorrectly?
Responses
Step 3: Student should have subtracted 6 from both sides, not added 6.
Step 5: Student should have subtracted 6 from both sides, not divided by 6
Step 1: Student should have only distributed the 2 to the x and not the x & 3.
Step 2: Student should have added 2x + 3x = 5x, not 2 x 3 = 6x
Answer:
error in Step 2
Step-by-step explanation:
2(x - 3) + 3x = 19
Step 1 : 2x - 6 + 3x = 19 ← simplify left side by collecting like terms
Step 2 : 5x - 6 = 19 ← add 6 to both sides
Step 3 : 5x - 6 + 6 = 19 + 6
Step 4 : 5x = 25 ← divide both sides by 5
Step 5 : x = 5
Error was made by student in Step 2 who should have added 2x and 3x, not multiplied 2 × 3
A cash register in a certain clothing store is at the same distance from two dressing rooms in the store. The distance between the two dressing rooms is 16 feet, which of the following could be the distance between the cash register and either dressing room?
I. 6 feet
II. 12 feet
III. 24 feet
(A) I only
(B) II only
(C) III only
(D) I and II
(E) II and III
The distance between the cash register and either dressing room could be 12 feet or 24 feet
The correct answer is an option (E) II and III
In this question, we have been given a cash register in a certain clothing store is at the same distance from two dressing rooms in the store.
The distance between the two dressing rooms is 16 feet.
We need to find the distance between the cash register and either dressing room.
Let m be the distance between the cash register and either dressing room.
Since, a cash register in a certain clothing store is at the same distance from two dressing rooms in the store.
assuming cash register and both the dressing rooms are linear we get an equation,
m + m = 16
2m = 16
m = 8 feet
If cash register and both the dressing rooms are not linear, then the distance between the cash register and either dressing room must be greater than 8 feet.
Therefore, the distance between the cash register and either dressing room is either 12 feet or 24 feet
Learn more about an equation here:
https://brainly.com/question/649785
#SPJ4
6.334*104=6.334*10<sup>4</sup>=
Answer:
what's that
Step-by-step explanation:
What is the Minimum value of k=
Answer:
k = -3
Step-by-step explanation:
Lines in the form y=k are horizontal. The lowest point on the parabola has a y-value of -3. That is the value where y=-3 will intersect the parabola at exactly one point. Every k value above this will have 2 points of intersection.
Ali, Basti and Cian stand at three points A, B and C respectively. Suppose that the measure of angle ABC is 50 degrees , the measure of angle BAC is 60 degrees and Ali is exactly 150 ft away from Basti. Find the distance between Basti and Cian.
To find the distance between Basti and Cian, we can use the law of sines in triangle ABC. The law of sines states that the ratio of the length of a side to the sine of the opposite angle is constant for all sides and their corresponding angles in a triangle.
Let's label the distance between Basti and Cian as "x". We know that the measure of angle ABC is 50 degrees and the measure of angle BAC is 60 degrees. We also know that Ali is exactly 150 ft away from Basti.
Using the law of sines, we can set up the following equation:
sin(50°) / 150 = sin(60°) / x
To solve for "x", we can rearrange the equation:
x = (150 * sin(60°)) / sin(50°)
Using a calculator, we can evaluate the expression:
x ≈ (150 * 0.866) / 0.766
x ≈ 168.4 ft
Therefore, the distance between Basti and Cian is approximately 168.4 ft.
A bag contains 5 red marbles, 7 blue marbles and 2 green marbles. If two marbles are
drawn out of the bag, what is the probability, to the nearest 1000th, that both
marbles drawn will be blue?
Answer:
0.218
Step-by-step explanation:
The expression below represents the profit, in dollars, a movie theater makes when n customers attend a movie
3.5n-175 which of these is an equivalent expression that reveals the number of customers required for the movie theater to break even (have a profit of $0)?
A.3.5(n-175)
B.3.5(n-50)
C.-171.5n
D.175-3.5n
Answer:
a
Step-by-step explanation: